2016 Obama's America [videorecording (DVD)] : love him, hate him, you don't know him - D'Souza, Dinesh, 1961-; Sullivan, John (Filmmaker) (Lionsgate, 2012)
Based on the work of Dinesh D'Souza, 2016: Obama's America is the highest-grossing conservatively-slanted documentary of all time. It lays out what D'Souza believes Obama would do in a second term as President of the United States. He bases his conclusions on Obama's father's anti-colonialism and on Obama's purported psychological desire to fulfill his father's dream of diminishing the power of Western imperial states. The film is arresting in its presentation and sobering in its conclusions.